World War II in Europe. (World Book's documenting history, 2011)
"A history of World War II as it was fought in Europe, based on primary source documents and other historical artifacts. Features include period art works and photographs; excerpts from literary works, letters, speeches, broadcasts, and diaries; summary boxes; a timeline; maps; and a list of additional resources"--Provided by publisher.